1994
DOI: 10.1002/tox.2530090104
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin‐producing fungi associated with Nigerian maize

Abstract: Maize samples were obtained from different locations-namely Aba, Abakaliki, Afikpo, Okigwe, and Owerri-all in southeast Nigeria. Twelve mold species of the genera Aspergillus, Penicillium, Cladosporium, Alternaria, Fusariurn, and Acremoniurn (Cephalosporiurn) were isolated. The presence of aflatoxin B, was detected in 80% of the samples by the characteristic blue fluorescence that appeared on silica gel coated thin layer chromatography plates when viewed with a long-wave ultraviolet radiation source alongside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Different species of the genera Aspergillus, Penicillium, Cladosporium, Alternaria, Fusarium and Acremonium were isolated in maize grains samples from Kano and Plateau Opadokun and Ikeorah ( 1983 ), as well as from Aba, Abakaliki, Afikpo, Okigwe and Owerri – all in southeast Nigeria by Aja‐Nwachukwu and Emejuaiwe ( 1994 ). These fungi species are implicated as aflatoxicogenic in common foodstuff.…”
Section: Mycotoxins Contamination Of Food and Feeds In Nigeriamentioning
confidence: 99%
“…Different species of the genera Aspergillus, Penicillium, Cladosporium, Alternaria, Fusarium and Acremonium were isolated in maize grains samples from Kano and Plateau Opadokun and Ikeorah ( 1983 ), as well as from Aba, Abakaliki, Afikpo, Okigwe and Owerri – all in southeast Nigeria by Aja‐Nwachukwu and Emejuaiwe ( 1994 ). These fungi species are implicated as aflatoxicogenic in common foodstuff.…”
Section: Mycotoxins Contamination Of Food and Feeds In Nigeriamentioning
confidence: 99%
“…The foods at highest risk of aflatoxin contamination are corn, peanut and cotton seed 5 . Aflatoxin B1 has been detected in 80% of maize samples obtained from different locations in Southeast Nigeria 6 and similarly 92 % of animal feed samples taken from commercial sources in Thailand were contaminated with aflatoxin B1 7 . In at least three parts of the world, East Africa, the Philippines and Thailand, good epidemiological evidence has been collected showing a correlation between the incidence of liver cancer and exposure to aflatoxins 5 .…”
Section: That Can Invadementioning
confidence: 99%
“…Though the risk is major, it is unappreciated by those residing in these third world countries as reported by Bandyopadhyay et al (2007). A survey conducted on maize in Southeast Nigeria indicated that 80% of samples from different locations in the area were aflatoxin contaminated (Aja-Nwachukwu and Emejuaiwe, 2006); while that on street vended corn and groundnut-based snacks in Lagos showed 36% contamination with total aflatoxins exceeding permissible limits for the country (Ezekiel et al, 2012) . Similar experiment in Thailand showed that…”
Section: Introductionmentioning
confidence: 99%